ANALISIS FISIK, KIMIA DAN SENSORIS TEH BUNGA KRISAN PUTIH (Chrysanthemum morifolium Ramat.) DENGAN PENGERINGAN KABINET - Rofandi Hartanto; Skolastika RF Fitri; Kawiji Kawiji; Sigit Prabawa; Bambang Sigit; Bara Yudhistira (AGROINTEK, 2021)
White chrysanthemum (Chrysanthemum morifolium Ramat.) is widely used in medicine, popular drinks and as a functional food. White chrysanthemums are often used as health care products because they contain functional compounds such as phenolic compounds and antioxidant activity. Chrysanthemum is well known in Indonesia, but it has not been utilized optimally in daily life as functional food. This research is done in order to determine the effect of drying using cabinet dryer at temperatures of 40°C, 50°C, and 60°C on physical characteristics such as color and shrinkage, chemical characteristics such as moisture content, total phenol, antioxidant activity and water activity, and sensory characteristics such as color, aroma, taste, after taste and overall as well as the amount of heat required for the drying process. This research is conducted using completely randomized design. The results show that cabinet dryer at 60°C is the best drying method. Characteristics in white chrysanthemum tea are ∆E value is 39,51; long shrinkage value is 23,65%, width shrinkage is 28,46%; water content value is 6,81%; total phenol value is 15,99%; antioxidant activity value is 87,52%; water activity value is 0,25; with color 3,93 (like), aroma 3,30 (neutral), taste 3,03 (neutral), after taste 3,33(neutral) and overall 3,23 (neutral). The heat of drying at 60°C is 2.147,295kJ.